(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
The edition of the Statuta et ordines hospitalis seu mansionis Beatissimi Lazari of Parma of the 15th century authentic copy, but partly dating back to the 13th century, is an opportunity to enrich our knowledge of the lepers’ hospital both in its internal relations and in its relations with external society. The original characteristic, still firmly established in the 15th century, was that it was a religious community modelled from the outset on the monastic model. This model is evident, among other things, in the obedience that characterises the relationship between the sick and the minister. However, being a special reality, even compared to other hospitals, the figure of the minister/rector developed very strong coercive powers towards them. Men and women, forced into a forced cohabitation with no end but death, were rigidly disciplined, controlled and punished, not only in relation to deviant and violent ways of acting, but also in relation to behaviour that did not first and foremost respect a Christian morality. Definitely strong was the concern that the sick would infect the healthy, transgressing the rules that bound them to a compulsory residence and the renunciation of relations with outside society; but equally strong, or perhaps stronger, was the fear that violent dynamics, immoral behaviour and, not least, acting against the economic interests of the community itself would manifest.